Carbon Sequestration Potential of Natural Sandalwood Forest in Southern Western Ghats, India - B. Kalaiselvi; S. Dharumarajan; M. Lalitha; R. Vasundhara; R. Srinivasan; K.S. Karthika; Rajendra Hegde; Rameshan; K.S. Anil Kumar; Jagdish Prasad; N. Maddileti; Ranabir Chakraborty (Journal of the Indian Society of Soil Science, 2023)
Reliable estimation of soil carbon sequestration potential (CSP) is a prerequisite for carbon (C) management practices and climate-resilient sustainable agriculture. In the present study, the CSP of natural sandalwood forest, tea plantation and cropland soils were assessed by applying Hassink’s C saturation-deficit concept. Organic C associated with clay+silt fractions was estimated that ranged from 32 to 53% of total organic carbon (TOC). The C saturation potential ranged from 16 and 24.3 mg C g-1 soil, but did not show any significant differences among the land uses. The current C saturation (Ccur) associated with clay+silt particle sizes ranged from 19.9 to 24.3, 16.9 to 22.2 and 15.95 to 23.5 mg g-1 for tea plantation, sandalwood forest and agricultural lands, respectively. The cumulative CSP of top 100 cm soils was found high in agricultural lands (189-262 Mg C ha-1), followed by sandalwood forest lands (56-116 Mg C ha-1) and tea plantations (83.3 Mg C ha-1). This study demonstrates that croplands are an effective option to achieve high C saturation potential as they are highly C deficient, allowing C emission to be controlled. Paramount attention must be given to C stabilization in the finer soil fractions. Adopting agroforestry systems in croplands could increase the C sequestration through above and below ground biomass deposition. Albeit the small data size and lack of validation, the present study can provide a baseline idea about the CSP of different land uses in Western Ghats, India.